2018
DOI: 10.1007/s10865-018-9912-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial complications of HIV/AIDS-metabolic disorder comorbidities among patients in a rural area of southeastern United States

Abstract: As people living with HIV (PLWH) experience longer life-expectancies resulting from antiretroviral therapy, comorbid conditions are increasing, particularly metabolic disorders. There is potential for psychosocial factors such as stigma experiences, depression, and alcohol use to complicate both HIV infection and metabolic disorders, including diabetes mellitus and hyperlipidemia. While the impact of these psychosocial factors on HIV infection alone are widely studied, their role in potentially complicating HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Applying an intersectional lens, this separation fails to acknowledge clients' complex health experiences and the interaction between HIV and other medical conditions that disproportionately impact those who are most marginalized in a particular socio-political context [12,48,49]. The burden of seeking separated care may be especially harmful consid-ering that those with less access to HIV prevention services and HIV education, such as those in rural communities and burdened by class oppression, are disproportionately likely to have comorbid healthcare needs and more adverse HIV outcomes [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Applying an intersectional lens, this separation fails to acknowledge clients' complex health experiences and the interaction between HIV and other medical conditions that disproportionately impact those who are most marginalized in a particular socio-political context [12,48,49]. The burden of seeking separated care may be especially harmful consid-ering that those with less access to HIV prevention services and HIV education, such as those in rural communities and burdened by class oppression, are disproportionately likely to have comorbid healthcare needs and more adverse HIV outcomes [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Other observations showed that after various interventions of AIDS patients, their HIV-1 RNA expression level and viral load were drastically altered [42], and HIV-1 RNA and viral load can be used to evaluate the prognosis effect of AIDS patients. Another study found that HIV infection can lead to significant reduction of CD4 + /CD8 + ratio [43]. The reduction of CD4 + /CD8 + ratio indicated that the immune function was markedly decreased, which promotes the further increase of HIV-1 RNA expression, indicating an interplay between HIV-1 RNA and CD4 + /CD8 + .…”
Section: Disease Markersmentioning
confidence: 97%
“…The positive correlations between depression and posttraumatic symptoms, internalizing stigma and number of traumatic experiences, are not surprising. Several studies have demonstrated the comorbidity of stigma, depression, and posttraumatic stress symptoms in primary care settings [51-53].…”
Section: Discussionmentioning
confidence: 99%